2012
DOI: 10.1007/s12088-012-0321-8
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic Structural Changes in Paddy Straw Pretreated with Trichoderma reesei MTCC 164 and Coriolus versicolor MTCC 138

Abstract: The present study reports the pretreatment of paddy straw by Trichoderma reesei MTCC 164 and Coriolus versicolor MTCC 138 to observe the changes in chemical composition and its correlation with change of surface structure, morphology and porosity of paddy straw. Compared with untreated straw, cellulose decreased by 15.9 and 19.3 % in T. reesei MTCC 164 and C. versicolor MTCC 138 pretreated paddy straw respectively. Lignin content increased by 41.4 % in T. reesei pretreated paddy straw whereas decreased by 19.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…In addition, the amount of cellulose decreased because the amorphous region in cellulose was decomposed. The decrease in the crystallinity of the cellulose occurred because the hydrogen bonding among cellulose, hemicellulose, and lignin was fractured . The plasticity of RS was improved by the inoculant and the mechanical properties of its composites.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the amount of cellulose decreased because the amorphous region in cellulose was decomposed. The decrease in the crystallinity of the cellulose occurred because the hydrogen bonding among cellulose, hemicellulose, and lignin was fractured . The plasticity of RS was improved by the inoculant and the mechanical properties of its composites.…”
Section: Resultsmentioning
confidence: 99%
“…However, only 120 kg ha -1 of Si were returned to our experimental field as RSC. Phutela and Sahni (2013) showed that fungi promote the solubilization of Si components in rice straw, which faster than that of other nutrients (N, P, K, Ca, Mg, Fe, Zn, Mn, Cu) when rice straw is continuously removed from paddy fields in the Mekong Delta. Our data on available Si concentrations in the surface (0 -10 cm) layer (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, Wickramasinghe and Rowell 22 demonstrated that rice straw added to soil suspensions increased the silicon concentration during incubation. Phutela and Sahni 15 showed that fungi promotes the solubilization of silica components in rice straw.…”
Section: Discussionmentioning
confidence: 99%